THE EDUCATION OF ANTI-CORRUPTION IN SECONDARY SCHOOL - Sukidin Sukidin; Wiwin Hartanto; Mukhamad Zulianto; Pudjo Suharso; Rizki Febri Andika Hudori (Economic Education, University of Jember, 2022)
Corruption prevention can be done by changing attitudes and behavior towards anti-corruption. Changing anti-corruption attitudes and behavior can be done through anti-corruption education in schools. The purpose of this study is to describe an anti-corruption culture in schools. This research was conducted using naturalistic inquiry methods. The results of this study the main task of anti-corruption education in schools is to provide knowledge to teach how to recognize corruption (and separate it from other types of crime), give arguments on why corruption is a crime, and show how to reduce fraud. In conclusion, Anti-corruption education can be integrated into the contents of the civic, social education curriculum, or separately in extra-curricular activities. It must be based on value learning and contextual teaching.